Peningkatan Kemampuan Siswa dalam Menulis Teks Deskripsi melalui Model Pembelajaran Quantum Writing - Juaidah Agustina; Hayatun Nufus; Rumita Rumita (ESTETIK : Jurnal Bahasa Indonesia, 2023)
This study aims to find out how the quantum writing method can help improve the ability to write descriptive text in junior high school students. This study took the case of class VII students of MTs Nurul Ula Burai. The population in this study were all 47 class VII students of MTs Nurul Ula Burai. The sample in this study was obtained using cluster random sampling technique. So that class VII 1 with a total of 22 students was chosen as the experimental class and VII 2 with a total of 25 students as the control class. This study uses the experimental method. The data analysis technique used is the test data analysis technique and documentation. The results showed that the average value of the test results (experimental class) that used the quantum writing method in the ability to write descriptive text with an average test result score of 82.88, was higher than the control class that did not use the quantum writing method with an average score of average test result 62.62. For the results of hypothesis testing using the T test, it is known that the t-count is 8.20 compared to the t-table of 2.01, so the results of the t-count are greater than the t-table (8.20 > 2.01), so it can be concluded that the model learning quantum writing has a major influence on improving the ability to write descriptive texts for junior high school students.